Voix, corps et « amours nomades » : Les femmes du désert et les ambiguïtés du regard d’Isabelle Eberhardt - Vanezia Pârlea (Viatica)
This article examines Isabelle Eberhardt’s last work, the travelogue Sud Oranais, in order to shed some light on her views and representations of the “women of the desert”. Her perspective proves to be quite complex and ambiguous, mixing the depreciatory stereotypes with a more compassionate and empathetic attitude towards them.